Understanding metal organic chemical vapour deposition of monolayer WS2: the enhancing role of Au substrate for simple organosulfur precursors. Issue 43 (3rd November 2020) - Fan, Ye; Nakanishi, Kenichi; Veigang-Radulescu, Vlad P.; Mizuta, Ryo; Stewart, J. Callum; Swallow, Jack E. N.; Dearle, Alice E.; Burton, Oliver J.; Alexander-Webber, Jack A.; Ferrer, Pilar; Held, Georg; Brennan, Barry; et al.
Abstract : A deconstructed MOCVD model process allows in- operando fingerprinting of the chemical reactions that underpin WS2 monolayer crystal growth, and highlights the enhancing role of Au support in conjunction with simple organosulfide precursors. Abstract : We find that the use of Au substrate allows fast, self-limited WS2 monolayer growth using a simple sequential exposure pattern of low cost, low toxicity precursors, namely tungsten hexacarbonyl and dimethylsulfide (DMS). We use this model reaction system to fingerprint the technologically important metal organic chemical vapour deposition process by operando X-ray photoelectron spectroscopy (XPS) to address the current lack of understanding of the underlying fundamental growth mechanisms for WS2 and related transition metal dichalcogenides. Au effectively promotes the sulfidation of W with simple organosulfides, enabling WS2 growth with low DMS pressure (<1 mbar) and a suppression of carbon contamination of as-grown WS2, which to date has been a major challenge with this precursor chemistry. Full WS2 coverage can be achieved by one exposure cycle of 10 minutes at 700 °C. We discuss our findings in the wider context of previous literature on heterogeneous catalysis, 2D crystal growth, and overlapping process technologies such as atomic layer deposition (ALD) and direct metal conversion, linking to future integrated manufacturing processes for transition metal dichalcogenide layers.